Ex vivo and simulator models teaching therapeutic ERCP and EUS: description of SOBED’s first course - Artifon, Everson L.A. (2016)
Teaching models in endoscopy are important tools to minimize risks derived from endoscopic procedures, taking into account that therapeutic endoscopy, also known as surgical endoscopy, has greatly developed during the last decade. This results from the fact that minimally invasive procedures present relevant contributions and promote more comfort to patients. In this context, ex vivo teaching models and virtual simulators are important tools to the safe acquisition of abilities. In this article, the Brazilian Society of Digestive Endoscopy presents and describes its first course of therapeutic ERCP and EUS in models of laboratory teaching.